Association between perceived social support and recovery among patients with schizophrenia. (2020) - El-Monshed, Ahmed; Amr, Mostafa
Abstract: Background: Recovery from schizophrenia is a recent concept that antagonizes the well rooted persuasion of the impossibility to recover from mental illnesses. Recovery is viewed as the final outcome for schizophrenic patients, implying long term absence of psychiatric symptomatology and suitable occupational and social functioning. Aim: This study aimed to find out the association between perceived social support and recovery among patients with schizophrenia. Methods: The study was carried out using a descriptive cross-sectional research design on a convenience sample of 176 schizophrenic patients at the department of psychiatry in Mansoura University Hospitals. Three tools were used in the current study. The first was related to socio demographic and clinical features of the studied patients, the second tool was Recovery Assessment Scale–Domains and Stages, and the third tool was Multidimensional perceived social support scale. Results: Both perceived social support subscales and total score had a statistically significant (≤0.001) association with recovery. Conclusion: The study provides evidence that the quality of the social support plays an important role in recovery among schizophrenic patients. Mental health services can provide social inclusion program for schizophrenic patients. Re-building of social relationships may be a major aim of psychiatric nursing interventions in mental health services.